2019
DOI: 10.1111/den.13577
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in acute variceal bleeding: Comparison of the AIMS65 score to established upper gastrointestinal bleeding and liver disease severity risk stratification scoring systems in predicting mortality and rebleeding

Abstract: Background and Aim Risk stratification is recommended in all patients with acute variceal bleeding (AVB). It remains unclear whether liver disease severity or upper gastrointestinal bleeding (UGIB) scoring algorithms offer superior predictive ability. We aimed to validate the AIMS65 score as a predictor of mortality in AVB, and to compare AIMS65 with established UGIB and liver disease severity risk stratification scores. Methods International Classification of Diseases, Tenth Revision codes identified patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
1
23
0
9
Order By: Relevance
“…Recently, it had been reported that the AIMS65 bleeding score could well predict the in-hospital mortality, length of stay and expenses of patients with upper GIB [22,24,25]. In particular, Robertson et al [26] found that the AIMS65 bleeding score had a good ability to predict the death of upper GIB(AUROC: 0.84). However, due to the limitation of sample size in our study, more data are needed to verify the predictive value of the new risk score model on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it had been reported that the AIMS65 bleeding score could well predict the in-hospital mortality, length of stay and expenses of patients with upper GIB [22,24,25]. In particular, Robertson et al [26] found that the AIMS65 bleeding score had a good ability to predict the death of upper GIB(AUROC: 0.84). However, due to the limitation of sample size in our study, more data are needed to verify the predictive value of the new risk score model on mortality.…”
Section: Discussionmentioning
confidence: 99%
“…20 HVPG > 20 mm Hg following variceal bleeding scientifically increases mortality. 1 Despite advances in its treatment, 6week mortality after variceal hemorrhage is still 15 to 20% in adults [21][22][23] compared with less than 10% in pediatric patients. [24][25][26]…”
Section: Pathophysiologymentioning
confidence: 99%
“…In this issue, Robertson et al 8 have reported the effectiveness of AIMS65 for risk stratification of poor clinical outcomes in patients with AVB. Herein, all the patients with presentation of AVB were risk-stratified using AIMS65, Rockall, pre-endoscopy Rockall (pre-Rockall), CTP, MELD and United Kingdom MELD scores on the first day of admission before index endoscopy.…”
mentioning
confidence: 99%
“…The aforementioned AIMS65, on the other hand, is a very straightforward scoring system for predicting outcomes of inpatients with UGIB. 8 Nevertheless, the endoscopy-oriented risk scores (endoscopic scores) including GBS, RS and AIMS65 had been synthesized for diverse concepts and different purposes, varying in causes of UGIB including AVB or NVUGIB; even based on either inpatient or outpatient status. We clinicians have felt unmet as most of the existing studies included only a small portion of AVB cohorts; very limited data regarding the prognostic predicting value with special reference to AVB are available.…”
mentioning
confidence: 99%
See 1 more Smart Citation